2009
DOI: 10.1002/ajmg.b.30908
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the dopamine receptor gene family on temperament traits in a population‐based birth cohort

Abstract: Although the genetic determinants of personality have been intensively investigated especially since Cloninger proposed his psychobiological model of temperament and character, findings to date remain inconclusive and very few studies have addressed the topic in large population cohorts. In the current study we investigated one gene family in its entirety by addressing the role of all known dopamine receptor genes, DRD1-DRD5, on Cloninger's temperament traits in a Finnish population-based birth cohort. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
3
14
0
Order By: Relevance
“…In particular, polymorphisms in DA and 5-HT receptors were associated with NS and HA. For instance, Noble et al (1998) Nyman et al (2009) found associations between several DRD2 gene SNPs and NS and HA traits in a Finnish cohort. Functional neuroimaging studies have shown that DRD2 binding in the right insular cortex was associated with NS scores in a Japanese population , while DRD2 binding in the amygdala was associated with HA .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, polymorphisms in DA and 5-HT receptors were associated with NS and HA. For instance, Noble et al (1998) Nyman et al (2009) found associations between several DRD2 gene SNPs and NS and HA traits in a Finnish cohort. Functional neuroimaging studies have shown that DRD2 binding in the right insular cortex was associated with NS scores in a Japanese population , while DRD2 binding in the amygdala was associated with HA .…”
Section: Discussionmentioning
confidence: 99%
“…As Cloninger et al (1993) predicted, NS is thought to be associated with dopaminergic (DA) activity, HA with serotonergic (5-HT) activity, and RD with noradrenergic (NE) activity. Indeed, genetic linkage studies have shown a positive relationship between these personality traits and genes that encode the aforementioned neurotransmitter receptors or transporters (Noble et al 1998;Strobel et al 2003;Kim et al 2007;Serretti et al 2007;Nyman et al 2009;Nakamura et al 2010); however, other studies found no significant associations. Nonetheless, there is an emerging consensus that global alterations in specific central neurotransmitter systems can influence personality traits.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [14] found a significant influence of the interaction between the two alleles of a DRD4 polymorphism on RD2 personality traits in young Korean females. Nyman et al [16] investigated the influence of the DRD4 VNTR and 23 SNPs of all known dopamine receptor (DRD1-DRD5) genes on personality traits in a large Finnish population, and found associations, strongest in females, between several SNPs at the 5′ end of DRD2 and HA, and between those at the 3′ end of DRD2 and RD2. Yasuno et al [19] also demonstrated a significant relationship between DRD2 binding in the amygdala and the HA personality trait using positron emission tomography in healthy Japanese males.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have also demonstrated that variants in the genes encoding proteins in the dopaminergic signaling system, including dopamine receptors, DRD2 [15,16], and DRD4 [12,13,17,18], dopamine transporter 1 [43], and COMT [10], have been linked to variability in NS trait scores in different healthy populations. Our team also showed an association between DARPP-32 polymorphisms and NS scores in a Chinese Han population [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation